Protocol for a cost–utility analysis of neurostimulation and intensive camp-based therapy for children with perinatal stroke and hemiparesis based on a multicentre clinical trial - Myla E Moretti; Patrick Berrigan; Jacquie Hodge; Adam Kirton; Wendy J Ungar; Jennifer D Zwicker (BMJ Open, 2021)
Introduction Perinatal stroke leads to cerebral palsy (CP) and lifelong disability for thousands of Canadian children. Hemiparesis, referring to impaired functionality in one side of the body, is a common complication of perinatal stroke. Standard long-term care for hemiparetic CP focuses on rehabilitation therapies. Early research suggests that patients with hemiparesis may benefit from adjunctive neuromodulation treatments such as transcranial direct current stimulation (tDCS). tDCS uses electric current to stimulate targeted areas of the brain non-invasively, potentially enhancing the effects of motor learning therapies. This protocol describes an economic evaluation to be conducted alongside a randomised controlled trial (RCT) to assess the incremental cost of tDCS added to a camp-based therapy compared with camp-based therapy alone per quality-adjusted life year (QALY) gained in children with hemiparetic CP.Methods and analysis The Stimulation for Perinatal Stroke Optimising Recovery Trajectories (SPORT) trial is a multicentre RCT evaluating tDCS added to a 2-week camp-based therapy for children aged 6–18 years with perinatal ischaemic stroke and disabling hemiparetic CP affecting the upper limb. Outcomes are assessed at baseline, 1 week, 2 months and 6 months following intervention. Cost and quality of life data are collected at baseline and 6 months and results will be used to conduct a cost–utility analysis (CUA). The evaluation will be conducted from the perspectives of the public healthcare system and society. The CUA will be conducted over a 6-month time horizon.Ethics and dissemination Ethical approval for the SPORT trial and the associated economic evaluation has been given by the research ethics boards at each of the study sites. The findings of the economic evaluation will be submitted for publication in a peer reviewed academic journal and submitted for presentation at conference.Trial registration number NCT03216837; Post-results.